Approximation of the Norton–Hoff plasticity model with isotropic hardening through Cosserat plasticity - Bies, P.M. (Archives of Mechanics, 2014)
In this paper the regularizing properties of Cosserat elasto-plastic models in a geometrically linear setting are investigated. For vanishing Cosserat effects it is shown that the Norton–Hoff model with isotropic hardening is approximated by the model with microrotations.